Is there a bank lending channel of monetary policy in Spain? - Ignacio Hernando; Jorge Martinéz Pagés (European Central Bank (ECB), 2001)
This paper uses panel data on banks, for the period 1991-98, to test the existence of a bank-lending channel in the Spanish economy. In order to distinguish between loan demand and supply movements, several exercises are performed. First, we analyse the differential responses, to monetary policy changes, of bank lending by banks with different size, liquidity and capitalisation. Second, we analyse the response to an exogenous deposit-reducing shock a tax-induced shift from deposits to mutual fund shares). As this involves a pure loan supply shock, it best solves the above-mentioned identification problem. Our results are mostly against the existence of a bank-lending channel in the period under analysis. This result appears to be related to the important role of many small banks as collectors of savings, meaning they have a large volume of resources available for lending
Keywords: C23; E44; E52; G21; 330; bank funding; bank lending; monetary transmission mechanism